TRIZ approach for designing a new assisted tooling for dimple structure fabrication / Mohd Nor Azam Mohd Dali...[et al.] - Mohd Dali, Mohd Nor Azam; A. Ghani, Jaharah; Che Haron, Che Hassan; Rizal, Muhammad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
TRIZ is a systematic means or tool that provides a logical approach to solving problems through inventive and innovative manners. This research shows the TRIZ approach implemented in demonstrating the need and necessity for developing the design and concept of assisted tooling, which is relatively new, in fabricating a dimple structure for the turning process. Based on the analysis using TRIZ, a structural design and concept of linearly speed movement assisted tooling was developed by using low cost mechanical components that are readily available and easily purchased in the market. Movement of the tool holder was in the x direction with the help of a DC motor connected to a cam system to move the tool holder. The factors for selecting this concept of structural design in this research were based on low component cost, efficiency, performance, durability, minimum use of supportive components, and a simple design installation which can be mounted on a tool post and turret without redesigning the tool holder and, therefore, minimised the cost of fabrication.